Investigating the application of thematic progression in EFL writing: a systematic review - Sun, Guodong; Ahmad, Norhakimah Khaiessa (Society for Research and Knowledge Management, 2024)
A systematic literature review was conducted to examine the studies on the application of thematic progression (TP) to EFL writing. Based on three criteria of research relevance, coverage and update frequency(Shaheen,2023), five databases were chosen, covering Web of Science, Scopus, Eric, Google Scholars and ProQuest. A total of 32 research articles published from 2014 to 2023 were categorized and reviewed. The research methodology mainly follows the guidelines of PRISMA to address the three research questions: 1) What are the development trends in TP -based EFL writing studies including research publications, countries and methodologies? 2) How is TP applied to EFL writing? 3)How does TP influence EFL writing performance? It was discovered that in the past decade there was a steady increase and expansion in the number of research articles and the range of research countries and methods. Moreover, different TP patterns were found to have been distributed across six writing types. These TP patterns established stronger relations with and strengthened writing organization, language use, and content. From the above findings, it can be suggested that TP-based EFL writing researches have regained their development momentum. It can also be inferred that the distribution of TP patterns varies from genre to genre and the patterns improve the overall EFL writing performance by enhancing writing organization, content and language use.